Market study on the development of a contemporary art marketplace in Brazil - Gribaudo, Edouard Clement Igor (2022)
Due to the great development of ecommerce in the world in the last decade, the digital sales channel has become essential in global economy. In emerging countries such as Brazil, the growth of online sales has recently been accelerated by the access to IT tools by millions of new users. The study will present how the Brazilian Contemporary Art market is developing, its place in the global market and how it should develop in the current market context. The research objective is to assess the feasibility of a Contemporary Art marketplace in Brazil. The initial focus of this research is on ecommerce phenomenon in the world and in Brazil, the Brazilian Art market and its Contemporary Art importance as well as the complexities of the Brazilian Art system. Then, the study will provide an overview of the online Art market acceleration, the marketplace as a new digital tool in Brazil as well as the opportunity to establish a Contemporary Art marketplace in Brazil. Several managers of Brazilian Contemporary Art galleries located in São Paulo, were interviewed through a questionnaire to understand the overall situation of the galleries and their future prospects. Although the majority of sales are made in physical galleries spaces, the slow development of online sales has limited the expansion of the local market. Sales costs do not correlate with revenue sources. However, there is a positive correlation between the desire to develop sales in value and the development of online sales channels. There is a contradiction between the opportunities of the online Contemporary Art market in Brazil and the decision of galleries to apply new digital methods and strategies. Finally, the study will propose the creation of a marketplace as the most appropriate digital tool for the sale of Contemporary artworks. This digital sales tool could be useful for the development of the local market before its global expansion and beneficial for all market players, taking into account market trends and system barriers.